Oil Palm Empty Bunch Compost as a Source of Humic Acid - Irma D. Oktavianta; Gusrizal Gusrizal; Nurlina Nurlina (Jurnal Akademika Kimia, 2020)
Humic acid is a fraction of humic compounds that are part of soil organic matter. In this research, humic acid is extracted from oil palm empty fruit bunches compost. Compost is made from the process of counting the empty oil palm bunches, which are composted until the compost is cooked. The humic acid extraction process uses a strong base extraction method. The principle of humic acid extraction is to dissolve the humic compound with a base solution and then separate it by adding an acid solution (HCl solution). The extraction of humic acid from oil palm empty fruit bunches compost produced blackish-brown humic acid with a yield of 4.895%. The result showed that the main functional group content of palm oil empty fruit bunches compost humic acid was the -OH group and phenol group which had a conjugated carbonyl group and a more aliphatic humic acid structure. Quantitatively, the functional groups of humic acid functional groups each amounted to a total acidity of 7,400 cmol/kg, a carboxylic group of 520 cmol/kg, and a phenolic -OH group content of 6,880 cmol/kg. Research results show that oil palm empty fruit bunches compost can be used as a source of humic acid.